MicroRNAs are suitable for assessment as biomarkers from formalin-fixed paraffin-embedded tissue, and miR-24 represents an appropriate reference microRNA for diffuse large B-cell lymphoma studies. Issue 3 (21st November 2012) - Culpin, Rachel Emily; Sieniawski, Michal; Proctor, Stephen John; Menon, Geetha; Mainou-Fowler, Tryfonia
Abstract : Tissue biopsy specimens in the form of formalin-fixed paraffin-embedded tissue (FFPET) represent a valuable resource for biomarker identification and validation. However, to date, they remain an underused asset due to uncertainty regarding RNA extraction and the reliability of downstream techniques, including quantitative RT-PCR. Recently, much interest has emerged in the study of microRNAs; small single-stranded RNAs with a role in transcriptional regulation, that are thought to be well preserved in FFPET. In this study, we show that microRNA expression is comparable between FFPET and matched fresh-frozen samples (miR-17-5p: p=0.01, miR-92: p=0.003), and demonstrate that no significant deterioration in expression occurs over prolonged FFPET storage (p=0.06). Furthermore, microRNA expression is equivalent dependant on RNA extraction method (p<0.001) or DNAse treatment of total RNA (p<0.001). Finally, we validate miR-24 as a suitable reference microRNA for diffuse large B-cell lymphoma (DLBCL) FFPET studies.